2012
DOI: 10.4172/2161-1459.1000110
|View full text |Cite
|
Sign up to set email alerts
|

A New Procedure for Diatom Extraction in the Diagnosis of Drowning

Abstract: A simple and economical procedure for the destruction of human organic material for the diatom examination is presented.The Author has tested a minimal amount of H 2 SO 4 diluted solution to detect diatoms in several tissues from human corpses under crime investigation, immersed in the sea and river water.The method was compared with a traditional method that includes digestion with a large amount of strong mixture of sulphuric and nitric acid (90%).The new procedure showed that all siliceous frustules of sea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Regarding the taxonomic composition (Fig. 2), the genera that had greatest number of valves were Pinnularia (38 specimens), which are benthic (epipelic) organisms [21], followed by Fragilaria (14), Actinocyclus (12), Cocconeis (5) and Encyonema (4). In the lung fragment, we found 32 genera, 6 species and 11 morphotypes, which due to its position in the chamber could not be identified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the taxonomic composition (Fig. 2), the genera that had greatest number of valves were Pinnularia (38 specimens), which are benthic (epipelic) organisms [21], followed by Fragilaria (14), Actinocyclus (12), Cocconeis (5) and Encyonema (4). In the lung fragment, we found 32 genera, 6 species and 11 morphotypes, which due to its position in the chamber could not be identified.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, drowning diagnostic studies using diatoms have advanced with the use of new methods of preparation and material analysis [12][13][14]. A review about the diagnosis of death by drowning using diatoms can be found in Donadel et al [15].…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of this method was that there was a decrease in the presence of destroyed diatoms fragments. The study showed that the classical acid digestion method used for the detection of diatoms was very aggressive and destroyed the diatoms frustules [17].…”
Section: Discussionmentioning
confidence: 99%
“…28 In the acid digestion method, there are some limitations and drawbacks due to the strong treatment of acids as the structure of diatoms may be destruct meanwhile an improved method were also developed that results good recovery and the ratio was defined as 3:1 of nitric acid to hydrochloric for the extraction of diatoms. [29][30][31][32]…”
Section: Extraction Of Diatoms From Water Samplesmentioning
confidence: 99%